2002
DOI: 10.1093/humrep/17.10.2673
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-dependent diabetes in men is associated with hypothalamo-pituitary derangement and with impairment in semen quality

Abstract: The reduced response of gonadotrophins to GnRH in diabetic men may indicate a decreased acute releasable pool of pituitary gonadotrophins. The results of TEM examination showed that sperm from men with diabetes presented severe structural defects in comparison with sperm from controls. It is possible that the reproductive impairment recognized in men with diabetes could be the result of interference by the disease on the hypothalamo-pituitary-testicular axis at multiple levels, as indicated by the reduced gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
114
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 27 publications
9
114
1
8
Order By: Relevance
“…Male infertility is a common complication of diabetes. The most frequent effects of DM on the male reproductive system include decreased levels of testosterone, lower testicular weight, abnormal spermatogenesis, alterations in sperm count and motility, and histopathological changes in testis tissue components [2][3][4][5] . Abnormalities in spermatogenesis due to increased apoptosis have been demonstrated in certain studies 2,3,[6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Male infertility is a common complication of diabetes. The most frequent effects of DM on the male reproductive system include decreased levels of testosterone, lower testicular weight, abnormal spermatogenesis, alterations in sperm count and motility, and histopathological changes in testis tissue components [2][3][4][5] . Abnormalities in spermatogenesis due to increased apoptosis have been demonstrated in certain studies 2,3,[6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…3 However, some investigators have described decreased testosterone levels, decreased pituitary response to GnRH and abnormal steroid feedback on hypothalamic-pituitary secretion. 6 In the present series, no patients had normozoospermia pre-transplantation, and the most frequent abnormalities were low sperm motility and morphological alterations. Most studies agree that diabetes is associated with disturbances in spermatogenesis.…”
mentioning
confidence: 40%
“…However, a large and diverse spectrum of abnormalities in all semen parameters including semen volume, sperm count, sperm motility and morphology has been reported. 6,7 A recent study has reported accumulation of advanced glycation end products in the reproductive tract of diabetic men. 8 However, the relationship between disease pathogenesis and reproductive function in men has not been well investigated and needs to be clarified.…”
mentioning
confidence: 99%
“…Baccetti et al (2002) have shown that DM significantly suppresses the HPG axis and lowers FSH and LH responses to exogenous gonadotropin releasing hormone (GnRH) in T1DM patients. Suppressed testosterone secretion as a result of diminished Leydig cell function (Pitteloud et al, 2005) has been reported in T2DM.…”
Section: Pre-testicular Effects Of Diabetes Mellitus (Hypothalamicpitmentioning
confidence: 99%